Synthesis of Vorinostat and cholesterol conjugate to enhance the cancer cell uptake selectivity. Issue 4 (15th February 2017) - Idippily, Nethrie D.; Gan, Chunfang; Orefice, Paul; Peterson, Jane; Su, Bin
Graphical abstract: A SAHA and cholesterol conjugate was designed and synthesized. The conjugate was loaded into low-density lipoprotein (LDL) particles and the biological activity was examined with cancer cell proliferation assay. The results indicate that the conjugate can be transported into cancer cells via LDL receptor and inhibits cancer cell growth. Abstract: Histone deacetylase (HDAC) inhibitors modulate various cellular functions including proliferation, differentiation, and apoptosis. Vorinostat (SuberAniloHydroxamic Acid, SAHA) is the first HDAC inhibitor approved by FDA for cancer treatment. However, SAHA distributes in cancer tissue and normal tissue in similar levels. It will be ideal to selectively deliver SAHA into cancer cells. Rapidly growing cancer cells have a great need of cholesterol. Low-density lipoprotein (LDL) is the major cholesterol carrier in plasma and its uptake is mediated by LDL-receptor (LDL-R), a glycoprotein overexpressed on the surface of cancer cells. Herein, we designed and synthesized a SAHA cholesterol conjugate, and further formed the conjugate containing particles with LDL as the carrier. The diameters of the particles were determined. The inhibitory activity of the particles carrying the conjugate was determined with cancer cell proliferation assay, and the hydrolysis of the conjugate by the enzymes in cancer cells was confirmed with LC–MS/MS.